Weipixiao attenuate early angiogenesis in rats with gastric precancerous lesions - Jinhao Zeng; Ran Yan; Huafeng Pan; Fengming You; Tiantian Cai; Wei Liu; Chuan Zheng; Ziming Zhao; Daoyin Gong; Longhui Chen; Yi Zhang (BMC Complementary and Alternative Medicine, 2018)
Abstract Background Angiogenesis is a pathobiological hallmark of gastric cancer. However, rare studies focus on angiogenesis in gastric precancerous lesions (GPL). Weipixiao (WPX), a Chinese herbal preparation, is proved clinically effective in treating GPL. Here, we evaluated WPX’s anti-angiogenic potential for GPL, and also investigated the possibility of its anti-angiogenic mechanisms. Methods HPLC analysis was applied to screen the major chemical components of WPX. After modeling N-methyl-N′-nitro-N-nitrosoguanidine (MNNG)-induced GPL in male Sprague-Dawley rats, different doses of WPX were administrated orally for 10 weeks. Next, we performed histopathological examination using routine H&E staining and HID-AB-PAS staining. In parallel, we assessed angiogenesis revealed by microvessel density (MVD) using CD34 immunostaining, and subsequently observe microvessel ultrastructure in gastric mucosa under Transmission Electron Microscope. Finally, we detect expression of angiogenesis-associated markers VEGF and HIF-1α using immunohistochemistry. Moreover, mRNA expressions of ERK1, ERK2, Cylin D1 as well as HIF-1α in gastric mucosa were determined by quantitative real-time reverse transcription- polymerase chain reaction. Results We observed the appearance of active angiogenesis in GPL rats, and demonstrated that WPX could reduce microvascular abnormalities and attenuate early angiogenesis in most of GPL specimens with a concomitant regression of most intestinal metaplasia (IM) and a portion of gastric epithelial dysplasia (GED). In parallel, WPX could suppress HIF-1α mRNA expression (P < 0.01) as well as protein expression (although without statistical significance), and could markedly inhibit VEGF protein expression in GPL rats. Mechanistically, WPX intervention, especially at low dose, caused a significant decrease in the ERK1 and Cylin D1 mRNA levels. However, WPX might probably have no regulatory effect on ERK2 amplification. Conclusions WPX could attenuate early angiogenesis and temper microvascular abnormalities in GPL rats. This might be partly achieved by inhibiting on the angiogenesis-associated markers HIF-1α and VEGF, and on the ERK1/Cylin D1 aberrant activation.